English Teachers' Perception and Classroom Practiceof Behaviourism Values in Bali Kiddy Primary School - Sukma, L.G.K. (Universitas Pendidikan Ganesha, 2018)
This study describes teachers’ perception regarding behaviourism values in teaching English for young learners in Bali Kiddy Primary School. This study involved 3 English teachers of Bali Kiddy Primary School. The objectives of this study were (1) to find out the perceptions of the English teachers in Bali Kiddy Primary School on behaviourism values in teaching English for young learners, (2) to find out how do the English teachers implement behaviorism values approach in teaching English as a foreign language in Bali Kiddy Primary School, and (3) to find out teachers’ perceptions about behaviourism values related to their strategies in teaching English for young learners in the classroom. The data was collected through observation sheets, questionnaires, and interviews. The research design was mix method. The data were analysed through descriptive qualitative which supported by quantitative data. The results indicated that the stated beliefs about behaviourism values in teaching English for young learner reflect their implementation in the classroom. There were some inconsistency between the perception and implementation based on teachers’ consideration on students’ condition